PENERAPAN KONSEP SMED (SINGLE MINUTES EXCHANGE OF DIES) DALAM PERGANTIAN TOOLING DI PT XYZ - Eko Sabtian Alfatah; Nurmala Rosalinda; Ely Stya Arga; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
The object of research used is the Blowmolding Department division, PT XYZ, with methods of observation, recording, and time study for each setup of change of activities carried out. Based on the data collection method, processing is carried out with the Single Minutes Exchange of Dies (SMED) method approach. The result of this study is that the majority of activities in the SMED method include internal activities, where in the setup process changes can be made to the work system. According to the activity category, it takes 3.28 hours while according to the work system category it takes 1.52 hours and 1.55 hours